UTILIZING LEARNING PLATFORMS AND BEHAVIOR ANALYSIS OF STUDENTS IN COMPLETING ASSIGNMENTS - Anisa Firda Khumaira; Mir’atun Nur Arifah (At-Thullab : Jurnal Mahasiswa Studi Islam, 2023)
The era of the industrial revolution 4.0 is closely related to the use of technology. In its development, technology is integrated into various sectors, one of which is the education sector. The use of technology in the field of education is shown by the development of various digital products that facilitate students in the learning process. This research tries to identify the various platforms used by students in their learning process, especially in helping them with their coursework. In addition, this research also reveals the advantages and disadvantages of platforms that are considered by students in utilizing the platform. This research is a descriptive qualitative research involving students of Undergraduate Program of Islamic Education at Universitas Islam Indonesia from various years informants. The informant determination technique was carried out through a purposive sampling technique and data collected through interviews. Analysis of the data that has been collected is carried out through data reduction, data presentation, and drawing conclusions. The results of this study indicate that; 1) The platforms used by students can be grouped based on the type of task activities. In coordination and discussion activities, students generally use WhatsApp, Zoom, and Google Documents. In the activity of writing academic papes, many students use Google Scholar and Researchgate. Meanwhile, for designing presentation slides, the platforms that are widely used are Slidesgo, Genially, and Canva. Apart from that, students also use Adobe Premiere, Adobe Illustrator, Coreldraw, VN Editor, Figma, SPSS, and Google Classroom to work on assignments with special criteria. 2) The advantages of the various platforms are practical, easy to use, facilitate group coordination, flexibility, foster creativity, and interesting. While the disadvantages are that some platforms need to be paid, the features are limited, some tools are difficult to use, require high device specifications, and not all platforms can be accessed offline.